Law Enforcement Efforts Against Fisheries Crime Under Specialist Lex Provisions in Indonesia - Siregar, Padian Adi (International Journal Reglement & Society (IJRS), 2020)
The 1945 Constitution (UUD) Article 33 paragraph (3) states, "The land and water and natural resources contained therein are controlled by the State and used for the greatest prosperity of the people. This writing uses normative juridical legal research methods (normative research). with a descriptive analytical research specification using secondary data. The data collection procedure is in the form of documentation of notes or quotations, tracing legal literature, books and others related to problem identification. The focus of the problem is how the provisions of Lex Fisheries Crime Handling Specialist in Indonesia? And how is the implementation of fisheries criminal law enforcement based on lex specialist provisions in Indonesia? Whereas the legal arrangements regarding evidence in criminal fisheries are regulated in Part Two A in Article 76 A, Article 76 B and Article 76 C of Law Number 45 of 2009 Tanteng Amendment to Law Number 31 of 2004 concerning Fisheries. Based on the sound of Article 76 A of Law Number 45 of 2009 Tanteng Amendment to Law Number 31 of 2004 concerning Fisheries, there are only two options for the choice of provisions regarding evidence in fisheries crime, the first is confiscated for the State or destroyed, based on this. , there is no provision for the return of evidence in a fishery crime against the perpetrator or his family. The system of criminal law enforcement in fisheries crime is included in specific provisions with provisions in specific laws. Not only on the provision that Fisheries Crime is regulated in a special law, because of the vast area of the Indonesian Sea, the government has given authority to various state institutions that oversee Indonesia's maritime sovereignty ranging from domestic threats to threats that come from within the country in particular. in fisheries crime, among others Polair, TNI-AL dan PPNS.